Pengembangan Multimedia Interaktif Mata Pelajaran Informatika Pada Kurikulum Sekolah Penggerak Untuk Siswa Kelas X SMA - Ahmad Yusuf; Syafril Syafril; Zuwirna Zuwirna; Abna Hidayati (Journal of Pedagogy and Online Learning, 2022)
Learning informatics sub-material algorithms and programming in the driving school curriculum has a change from visual programming to textual language in class IX, and in programming learning in class X students will learn the concepts of coding and procedural programming. In learning infomatics is still monotonous because the explanation of the material still uses e-books and books that have been provided by the government about Algorithms and Programming. Therefore, the author is interested in designing interactive multimedia, so that students better understand the learning material that is packaged interactively.This type of research is research and development or what is known as Research and Development (R&D). Based on the results of the material assessment from teachers of informatics subjects of SMA N 2 Padang and media experts lecturers of the Department of Curriculum and Educational Technology of UNP, there is a procurement of validation with the suitability of the material calculated from the average validator of 4.79 with the criteria of "very valid". There are two validators with the criteria of "very appropriate" with the value obtained from validator I of 4.62 and validator II of 4.87. For practicality analysis, it was taken through a questionnaire of responses from class X SMA N 2 Padang students related to the use of multimedia which was calculated to reach an average score of 4.62, so that the results of the practice could be known with the criteria of "very practical".